ANALISIS KINERJA PADA SIMPANG TIGA TAK BERSINYAL JALAN RAYA PLOSO - Sakti Sakti; Titin Sundari; Totok Yulianto; Meriana Wahyu Nugroho (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Jalan Raya Ploso, classified as a two-lane undivided road, serves as the primary route connecting Jombang Regency, Mojokerto Regency, and Lamongan Regency. This road is situated in a densely populated area that includes residential neighborhoods, commercial establishments, a terminal, and various vendors, resulting in a mix of vehicles such as large trucks, buses, motorcycles, and cars moving simultaneously. Traffic congestion frequently occurs due to several factors, including market activities, vehicle parking, and vehicles moving slowly or entering and exiting properties along the road. The aim of this research is to analyze the issues occurring on Ploso Highway and provide alternative solutions that can be implemented. The focus of the study is the unsignalized three-way intersection in front of Ploso Market. Observations indicated a road capacity of 2558 vehicles per hour (vph) with a degree of saturation (Dj) of 0.92. Since this degree of saturation does not meet the PKJI 2023 standard, which sets an ideal degree of saturation below 0.85, the researcher proposes an alternative solution involving widening the lane by 1.20 meters on the major road and 0.50 meters on the minor road.